ATP-citrate lyase promotes axonal transport across species - Aviel Even (Nature Portfolio, 2021)
Microtubule tracks are important for the transport of molecules within axons. Here, the authors show that ATAT1, the enzyme responsible for acetylating a-tubulin, receives acetyl groups from ATP citrate lyase whose stability is regulated by Elongator, a protein mutated in the neuronal disease Familial dysautonomia.